ANTIBIOTICS RESIDUE TEST ON THE LIVER OF BALI CATTLE IN SOME TRADITIONAL MARKETS IN BALI PROVINCE - Cundawan, Alexander Jacky; Siswanto, Siswanto; Sudira, I Wayan (Buletin Veteriner Udayana, 2020)
The presence of antibiotic residues in food of animal origin (eg. bali cattle liver) is closely related to the use of antibiotics for the treatment of diseases and use as feed additives. This study is a survey that aims to determine whether there is antibiotic residue in the liver of Bali cattle marketed in several regional markets in Bali Province, namely Jembrana, Singaraja, Tabanan, Gianyar and Karangasem districts. This study used 30 samples taken randomly, 6 samples from 2 markets in 1 district. Sampling conducted 3 repetitions on each market with different traders. Testing of antibiotic residues using bioassay test method (screening test). The results showed that Bali's liver cattle marketed in several regional markets in Bali Province did not contain antibiotic residues.